Spring Sonata - Hafizoah, Kassim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
1 – 6 April 2012. A Spring is a season blossomed with flowers, and visiting a country known for its beautiful spring is a must. Amidst busy teaching schedule, CMLHS organized a four-day and five-night Muslim Educational Tour to Korea from 1 – 6 April 2012.